Elucidating the knowledge, attitude, and stigma associated with tuberculosis: a community based descriptive study in Wau and Jur River, South Sudan - Peter Michael Marin; Morten Tryland; Musso Munyeme; Ambrose Samuel Jubara; Enock Matovu; Peter Waiswa; Javier Sanchez Romano; Francis Mutebi; David Onafruo; Estella Kitale; Esther Sabbath; Kayla J. Buhler; et al. (Tropical Medicine and Health)
Abstract Background Tuberculosis (TB) is a major public health problem in South Sudan. Inadequate knowledge, negative attitudes and perceived stigma may complicate the prevention efforts. This study describes knowledge, attitude, and stigma associated with TB among communities in Wau and Jur River, South Sudan. Methods From March to May 2023, a cross-sectional study was conducted among 352 community members randomly selected from residential blocks. A validated structured questionnaire was used to collect the required data. Descriptive, bivariate and multivariate analyses were performed. Results Out of 352 respondents, 51% (n = 180) were males and 49% (n = 172) were females. Majority 227 (64.5%) had poor knowledge about TB, meanwhile hearing about TB, age and level of education were associated factors. Fear of having TB was the major negative attitude (57.1%; n = 218), and most of the respondents (n = 327; 92.9%) had a perceived stigma towards TB, voicing that they disliked drinking or eating with people with TB and/or felt uncomfortable and kept their distance from people with TB. Conclusions Communities have little knowledge, negative attitude and perceived stigma towards people with TB. Hence, tailored health messages using local languages, training of community volunteers to reach villages without accessibility and communication network are essential to improve TB prevention and control in South Sudan.